The Impact of Social Media on Consumer Behavior in the Indian Tourism Sector: A Systematic Review Using the PRISMA Approach - Mansi Gupta, (European Economic Letters (EEL), 2024)
Social networking has significantly transformed multiple sectors, including the tourism industry. This review study seeks to examine the influence of social media on consumer behaviour in the Indian tourist sector. This paper conducts a systematic review using the PRISMA model to analyse existing literature. The objective is to gain a thorough understanding of how social media impacts the decision-making process, preferences, and travel patterns of Indian tourists.This study not only summarizes the existing research but also highlights areas where the literature is lacking and proposes potential avenues for further research. The study seeks to add to scholarly discourse and provide practical insights for tourism professionals and policymakers on how to effectively use social media to enhance the travel experiences of Indian tourists.